Cascade aza-Michael Addition-Cyclizations; Toward Renewable and Multifunctional Carboxylic Acids for Melt-Polycondensation - Noordzij, Geert J.; Wilsens, Carolus H. R. M. (Frontiers in Chemistry, 2019)
Although the aza-Michael addition reaction on various unsaturated (di-)carboxylic acids and esters of, for example, itaconic acid, is well known, the consecutive cyclization reaction has not received much attention in literature. The products of this aza-Michael cascade reaction, being mono- or di-carboxylic acid or ester functionalized N-alkyl-pyrrolidone structures, prove interesting for melt-polycondensation reactions as they exhibit excellent stability at elevated temperatures. In other words, this reaction is a toolbox for the generation of renewable monomers and, in turn, polymers with tunable physiological properties. Therefore, this work provides an overview of the state-of-the-art of the cascade aza-Michael addition-cyclization reactions on biobased unsaturated acids and esters, and their use in polymerization reactions. Furthermore, we extend this overview with the cascade aza-Michael addition-cyclization reaction of trans-trimethyl aconitate with di-amines to form a tetra-functional N alkyl-bis-(pyrrolidone dimethylcarboxylate), which exhibits excellent thermal stability and could effectively be used as monomer in polycondensation reactions. Importantly, the aza-Michael addition reaction between primary amines and trans-trimethyl aconitate can be considered a click-reaction; it proceeds quantitatively within minutes under ambient conditions and follows the principles of green chemistry.